2016
DOI: 10.3389/fnmol.2016.00036
|View full text |Cite
|
Sign up to set email alerts
|

Connexin30.2: In Vitro Interaction with Connexin36 in HeLa Cells and Expression in AII Amacrine Cells and Intrinsically Photosensitive Ganglion Cells in the Mouse Retina

Abstract: Electrical coupling via gap junctions is an abundant phenomenon in the mammalian retina and occurs in all major cell types. Gap junction channels are assembled from different connexin subunits, and the connexin composition of the channel confers specific properties to the electrical synapse. In the mouse retina, gap junctions were demonstrated between intrinsically photosensitive ganglion cells and displaced amacrine cells but the underlying connexin remained undetermined. In the primary rod pathway, gap junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 59 publications
(105 reference statements)
1
21
1
Order By: Relevance
“…First, it was essentially impossible to obtain a good fit of the current responses of the models to the physiological recordings obtained before and during onset of the action of MFA, suggesting that the physiologically recorded responses are markedly influenced by the electrical coupling. Second, whereas an alternative strategy could be to record from AII amacrine cells in the retina of genetically modified mice that lack Cx36 (the connexin involved in gap junction coupling of both AII amacrines and ON-cone bipolar cells), there is evidence that tracer coupling may not be completely abolished in Cx36 knockout mice (Deans et al 2002), potentially consistent with the suggestion that coupling between AII amacrines could involve additional connexins (Meyer et al 2016), or that compensatory mechanisms in knock-out animals could be triggered and influence expression of other connexins.…”
Section: Discussionmentioning
confidence: 72%
“…First, it was essentially impossible to obtain a good fit of the current responses of the models to the physiological recordings obtained before and during onset of the action of MFA, suggesting that the physiologically recorded responses are markedly influenced by the electrical coupling. Second, whereas an alternative strategy could be to record from AII amacrine cells in the retina of genetically modified mice that lack Cx36 (the connexin involved in gap junction coupling of both AII amacrines and ON-cone bipolar cells), there is evidence that tracer coupling may not be completely abolished in Cx36 knockout mice (Deans et al 2002), potentially consistent with the suggestion that coupling between AII amacrines could involve additional connexins (Meyer et al 2016), or that compensatory mechanisms in knock-out animals could be triggered and influence expression of other connexins.…”
Section: Discussionmentioning
confidence: 72%
“…This confirmed that binding of PDZ 10 of MUPP1 to mmCx36 is mediated by the PDZ binding domain at the very C-terminal end of the protein. Interestingly, while several studies 19 , 25 earlier reported that the truncated protein (mmCx36 S318 ter) fails to form gap junctions in transfected HeLa cells, the same construct assembled into gap junctions in HEK293 cells, suggesting that the assembly machinery differs between cell lines.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, we tested in cultured cells whether the phosphorylation of S315 has an influence on the size of gap junctions. As we have successfully used mmCx36 in a mammalian expression system to measure gap junction volume 25 and sequences for mouse and perch connexins are conserved with respect to the phosphorylated serine and PDZ binding domain (Fig. 1 b), we cloned an mmCx36 variant, in which S315 was mutated to aspartate (S315D) to mimic the phosphorylation of the serine residue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations